The Role of Community Health Workers in Maternal and Child Health Surveillance to Optimize Maternal and Child Health in Pasuruan District, East Java - Ninil Dwi Pangestu; Hermanu Joebagio; Setyo Sri Rahardjo (Masters Program in Public Health, Sebelas Maret University, 2017)
Background: Maternal mortality ratio, infant mortality rate, and underfive mortality rate are still high in Indonesia. Pasuruan is one of the districts in East Java with the highest infant mortality rate. One of the public health interventions that has been undertaken to address this issue is maternal and child health surveillance program with community health workers being the leading implementers. This study aimed to describe the role of community health workers in maternal and child health surveillance to optimize maternal and child health care services in Pasuruan District, East Java.Subjects and Method: This was a qualitative study using case study approach. It was conducted in Pasuruan, East Java. Key informants were selected by criterion sampling. The data were collected by in-depth interview, focus group discussion, observation, and document review. Data validity was checked by triangulation.Results: Community based maternal and child health surveillance program has been implemented for 4 years. However, only some of all community health workes have been trained in this program. The tasks of these community health workers included advocacy and monitoring of maternal and child health in the areas of posyandu. The implementation of these surveillance program had some obstacles, including low insentive of community health worker, inactive community health worker, lack of awareness among community members on maternal and child health issues, and medical factors of pregnant mothers that caused mortality.Conclusion: Community health workers help improve the quality of maternal and child health care by surveillance program, although their performances have yet to be enhanced.Keyword: maternal mortality rate, infant mortality rate, community health workersCorrespondence: Ninil Dwi Pangestu. Masters Program in Public Health, Sebelas Maret University, Jl. Ir. Sutami No. 36A Surakarta 57126, Jawa Tengah. E-mail: pangestu.ninil@gmail.com. Mobile +62856553737.Journal of Health Policy and Management (2017), 2(2): 128-136https://doi.org/10.26911/thejhpm.2017.02.02.04